2016
DOI: 10.29252/ijrm.14.3.193
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endometrial injury on first cycle IVF/ICSI outcome: A randomized controlled trial

Abstract: Background:Implantation remains a limiting step in IVF/ICSI. Endometrial injury isa promising procedure aiming at improving the implantation and pregnancy rates after IVF/ICSI. Objective:The aim of this study was to evaluate the effect of endometrial injury induced in precedingcycle on IVF/ICSI outcome.Materials and Methods:Four hundred patients undergoing their first IVF/ICSI cycle in two IVF units in Minia, Egypt were randomly selected to undergo either endometrial injury in luteal phase of preceding cycle (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
135
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(142 citation statements)
references
References 13 publications
4
135
1
2
Order By: Relevance
“…The risk of bias of the included RCTs is described in Table II. For seven RCTs, the risk of selection bias was unclear because the method of allocation was not clearly described (Karimzadeh et al , 2009; Baum et al , 2012; Inal et al , 2012; Singh et al , 2015; Mahran et al , 2016; Liu et al , 2017; Maged et al , 2018). Random sequence generation was interpreted to be at a low risk of selection bias because this was performed by computer-generated sequence (Narvekar et al , 2010; Safdarian et al , 2011; Inal et al , 2012; Nastri et al , 2013; Yeung et al , 2014; Gibreel et al , 2015; Singh et al , 2015; Tk et al , 2017; Maged et al , 2018), a table of random numbers (Baum et al , 2012; Liu et al , 2017), sealed envelopes (Mahran et al , 2016) or a bag of papers with equal amounts of intervention and control groups (Karimzadeh et al , 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias of the included RCTs is described in Table II. For seven RCTs, the risk of selection bias was unclear because the method of allocation was not clearly described (Karimzadeh et al , 2009; Baum et al , 2012; Inal et al , 2012; Singh et al , 2015; Mahran et al , 2016; Liu et al , 2017; Maged et al , 2018). Random sequence generation was interpreted to be at a low risk of selection bias because this was performed by computer-generated sequence (Narvekar et al , 2010; Safdarian et al , 2011; Inal et al , 2012; Nastri et al , 2013; Yeung et al , 2014; Gibreel et al , 2015; Singh et al , 2015; Tk et al , 2017; Maged et al , 2018), a table of random numbers (Baum et al , 2012; Liu et al , 2017), sealed envelopes (Mahran et al , 2016) or a bag of papers with equal amounts of intervention and control groups (Karimzadeh et al , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Since the publication of the abovementioned reviews, multiple RCTs on endometrial injury prior to ART have been carried out. While the first trials mainly focused on patients with RIF, more recent studies have shifted their focus to also include patients in earlier stages of IVF/ICSI treatment (Mahran et al , 2016; Liu et al , 2017; Tk et al , 2017; Maged et al , 2018). The increase in number of published studies not only calls for an updated review of the existing body of evidence, but also has created the possibility to subgroup patients according to the number of failed IVF/ICSI cycles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the most recent systematic review has reported no effect of the procedure on women undergoing IVF treatment with a previous one failed IVF cycle [23]. However, there is still uncertainty about the value of the procedure in women undergoing it for the first time [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Live birth and implantation rates were significantly lower in the control group than the study group (67% vs 28%, and 22.4% vs 18%, respectively). 16 In 2014, Yeung et al, evaluated 209 sub-fertile women with the first IVF-ET cycle, who underwent LEI with a biopsy catheter in the luteal phase preceding the IVF-ET cycle and no difference was reported in ongoing pregnancy rates of the study and control groups. 17 In these two studies, unlike our study, LEI was induced by a biopsy catheter in the luteal phase of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 99%